2020
DOI: 10.4103/1735-5362.288425
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of direct inhibitor of KRAS oncogenic protein by natural products: a combination of pharmacophore search, molecular docking, and molecular dynamic studies

Abstract: Background and purpose: Aberrant signaling by oncogenic RAS proteins occurs in almost all human tumors. One of the promising strategies to overcome such cancers is the inhibition of KRAS protein, a subtype of RAS family involved in cell growth, differentiation, and apoptosis, through preventing its effector, SOS1, from being attached to the protein. Experimntal approach: Herein, a virtual screening process was performed using pharmacophore search, molecular docking, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Recent studies have reported the certain natural compounds that are effective against the KRAS-linked upstream and down-stream signalling pathways that are directly or indirectly linked with cell proliferation, division, and apoptosis (24,25). We are now developing another compound (named STAR2) that shows low toxicity, and is effective against all mtKRAS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the certain natural compounds that are effective against the KRAS-linked upstream and down-stream signalling pathways that are directly or indirectly linked with cell proliferation, division, and apoptosis (24,25). We are now developing another compound (named STAR2) that shows low toxicity, and is effective against all mtKRAS cells.…”
Section: Discussionmentioning
confidence: 99%